Research on Solving Path of Negative Effect of “Information Cocoon Room” in Emergency - Wei Liu; Wei Zhou (Discrete Dynamics in Nature and Society)
The “information cocoon” can hinder the normal dissemination and flow of emergency information during emergencies. It is important to explore the factors of this effect and to resolve the negative effects of the information cocoon, so as to help the public to “break out of the cocoon” and help the government to better promote emergency information management. Based on information ecology theory and the S-O-R model, this study designed questionnaires using a Likert five-level scale and selected 388 publics from several smart city pilot areas in Changsha, Zhuzhou, Shaoshan, and Yueyang cities in Hunan Province. Field research was conducted based on four factors, information ontology, information technology, government regulation, and social network, and empirical analysis was conducted through structural equations. The study shows that information ontology, information technology, government regulation, and social networks have significant effects on the information cocoon effect by influencing the reinforcement of public information preferences. Among them, government regulation (P = 0.34) has the most significant effect on the reinforcement of public information preferences, followed by information ontology (P = 0.32) and social networks (P = 0.31), and information technology (P = 0.29) has the weakest effect. Combining the results of empirical analysis, we propose a four-dimensional path of “information-technology-regulation-value” to break the cocoon. By optimizing information ontology, using technology for good governance, promoting algorithmic fairness, and enhancing social stickiness, we help the public break through the shackles and negative effects of the information cocoon and promote the harmonious, stable, and healthy development of the emergency information field.